Rethinking Error Treatment: Written Corrective Feedback and Its Effects on EFL Learners’ Writing Proficiency - Marshinel Shiwani Nelson; Kristian Florensio Wijaya (Universitas Islam Negeri (UIN) Sultanah Nahrasiyah Lhokseumawe, 2026)
Employing meaningful types of feedback has been a customary pedagogical practice in modern EFL writing teaching and learning enterprises. With the help of constructive feedback, EFL learners are believed to be motivated to proceed into various challenging writing learning enterprises due to the profound realization of their specific writing strengths and weaknesses. Amongst these rewarding feedback models is WCF. Former educational researchers postulated that WCF could potentially promote more positive, conducive, and convivial writing learning climates to heterogeneous EFL learners due to its constructiveness and comprehensibility. The researchers initiated this small-scale library study to investigate the effects of WCF on the writing proficiency of EFL learners. To do so, the researchers capitalized on a thematic analysis method in reviewing 30 WCF studies to address more dependable, understandable, and employable findings to the designated research stakeholders. The thematically-subsumed research results implied that WCF helped EFL learners to improve their text quality, accuracy, and fluency. Through all these means, EFL learners are more likely to produce better-quality writing products in which they have been more cognizant decent writing models worth replicating during their idea generation process. These results indicated that WCF is beneficial for enhancing EFL learners’ writing proficiency as they have been more aware of the technical and acceptable aspects indispensable to be integrated in their designated writing compositions.